Efektifitas pendidikan kesehatan terhadap peningkatan pengetahuan remaja tentang dampak merokok - Salaman - Alfarisy; Agrina - -; Widia - Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study aims to determine the effectiveness of health education to the increasing knowledge about the effects of smoking teen. This research method, Quasi-experimental, with a pre-post study design with control group test. 74 samples were taken by using Quota  sampling technique. Measuring instrument used was a questionnaire with multiple choice questions. The analysis used univariate analysis with frequency distribution, and by using a bivariate dependent T test (paired sample test). The results showed that health education has a significant effect on the increase in knowledge about the effects of smoking adolescents p value 0.000. Based on these results suggestions for health workers to conduct health education in order to improve the knowledge of adolescents. Keywords    :  health education, level of knowledge, adolescent, cigarettes.